Antibiofilm and cytotoxic effect of 3,3′-dihydroxycurcumin (DHC) as photosensitizer agent in antimicrobial photodynamic therapy for endodontic purposes - Pereira, Jesse Augusto [UNESP]; Polaquini, Carlos Roberto [UNESP]; dos Santos, VanessaRodrigues [UNESP]; Caiaffa, Karina Sampaio [UNESP]; Rabelo, Rafaela Laruzo [UNESP]; Theodoro, Reinaldo dos Santos [UNESP]; Theodoro, Letícia Helena [UNESP]; Regasini, Luis Octavio [UNESP]; Duque, Cristiane [UNESP] (Elsevier, 2021)
Background: Curcuminoids have been designed not only to improve chemical and metabolic stability of curcumin (CUR), but also to increase its antimicrobial activity, without effecting its ability as photosensitizer agent in antimicrobial photodynamic therapy (aPDT) with light emitting diode (LED). This study evaluated the antimicrobial and antibiofilm action of curcumin analog DHC (or 3,3′-dihydroxycurcumin), submitted or not to LED irradiation, on microorganisms of endodontic importance and its influence on fibroblasts viability. Methods: DHC was synthetized by modified Pablon's methodology and the experiments were conducted under irradiation or not with indium gallium nitride-based LED (440-480nm, 100 mW/cm2, 0.78 cm2,60 s). The antimicrobial activity of CUR and DHC were determined by the Minimum Inhibitory and Bactericidal Concentration assays against Gram-positive and Gram-negative bacteria and the effect of both compounds on fibroblast viability was tested using colorimetric assays. They were also evaluated on 72h and 7days single-species biofilms and on 14 days multispecies biofilms formed inside dentin tubules by bacterial colonies counts and confocal microscopy, respectively. Data were analyzed statistically considering p<0.05. Results: DHC had bactericidal effect against all bacteria tested higher than CUR, in planktonic conditions. CUR and DHC (at 39 and 19 μg/mL, respectively) were cytocompatible and LED irradiation reduced fibroblast viability, regardless of compound. CUR and DHC reduced the growth of single-species biofilms and the effect of aPDT was bacteria dependent. DHC reduced more than 70% of microorganisms from multispecies biofilms, superior to CUR effect. Conclusions: DHC showed low cytotoxicity and antibiofilm effect similar to curcumin, when submitted or not to aPDT, and could be further explored as a bioactive compound for endodontic purposes.
Keywords: Biofilm; Curcumin; Curcuminoids; Cytotoxicity; Photodynamic therapy